The Use of the Drill Method with a Game-Based Learning Approach to Improve Mathematical Understanding and Foster Self-Confidence at Elementary School Level - Agustin Arum Setiyana; Muhtarom Muhtarom; Agus Sutono (Journal of Educational Sciences, 2026)
This study addresses low mathematical understanding and self-confidence among elementary school students in mathematics learning. Conventional instructional methods often lack engagement and fail to effectively support students' motivation and conceptual development. This research examines the effectiveness of combining the drill method with a game-based learning (GBL) approach to improve students' mathematical understanding and self-confidence. A quasi-experimental design was employed involving sixth-grade students from two elementary schools. The findings reveal that students who learned through the drill method integrated with game-based learning demonstrated significantly higher levels of mathematical understanding and self-confidence compared to those taught through conventional methods. Improvements in both cognitive and affective dimensions were more evident in the experimental group. These results indicate that integrating drill practices with game-based learning creates a more engaging learning environment and effectively enhances students' comprehension and confidence in mathematics. The study highlights the potential of interactive learning approaches as an innovative strategy to strengthen mathematics learning at the elementary level.